Experimental study of deformation and of effective width in axially loaded sheet-stringer panels - Ramberg, Walter (United States, 1939)
The deformation of two sheet-stringer panels subjected to end compression under carefully controlled end conditions was measured at a number of points and at a number of loads, most of which were above the load at which the sheet had begun to buckle. The two panels were identical except for the sheet, which was 0.070-inch 24ST Alclad for specimen 1 and 0.25-inch 24ST aluminum alloy for specimen 6. A technique was developed for attaching Tuckerman optical strain gages to the sheeet by the method of attachment. This technique was used to explore the strain distribution in the sheet at various loads. The twisting and the bending of the stringers were measured by means of pointers attached to the stringers. The shape of the buckles in the sheet of specimen 6 was recorded at two loads by means of plaster casts